Refleksi Moderasi Beragama dalam Perjalanan Suci Dhanghyang Dwijendra - juniawan, Heri; Suparta, Ida Kade (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2026)
The teachings regarding tolerance and harmony have long been explained in various religious literary texts, one of which is the text of Dharmayatra Dhanghyang Nirartha. Amidst religious pressures that are prone to conflict, it is necessary to study local wisdom and the universal values of religious texts to build a moderate religious life. Until now, the understanding of this text has primarily focused on historical aspects and has not been thoroughly studied from the perspective of the values of religious moderation. The purpose of this research is to study the moderating value of religion in the sacred journey of Dhanghyang Nirartha as contained in the text of Dharmayatra Dhanghyang Nirartha. The method used in this research is a literary study with a philological perspective, utilizing a book written in Balinese script entitled Babad Brahmana Catur kalih Dharmayatra Dhanghyang Nirartha as the main data source. The research results indicate that there are three essential values of religious moderation in the text, namely the value of humanity, the value of deliberation, and the value of justice.